2005
DOI: 10.1111/j.1439-0507.2005.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral zygomycosis

Abstract: Fifty-six patients with cerebral zygomycosis (mucormycosis) were seen during the period 1971-2001 in two tertiary care hospitals located in south India with tropical climate and catering to neurological diseases. Forty-four patients had rhinocerebral and twelve patients had isolated central nervous system (CNS) zygomycosis. Of these, ten were culture proven (Rhizopus oryzae in eight and Mucor in two); 30 were diagnosed as probable and 16 were diagnosed possible; mixed infections were seen in three patients. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 19 publications
3
83
0
5
Order By: Relevance
“…With respect to the clinical manifestations of cerebral zygomycosis, Sundaram et al reported headaches, fever, unilateral facial edema, visual disorders and loss of vision as the most frequent symptoms 5 . Although the patient in question showed a compatible clinical picture, it is also symptomatic of other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the clinical manifestations of cerebral zygomycosis, Sundaram et al reported headaches, fever, unilateral facial edema, visual disorders and loss of vision as the most frequent symptoms 5 . Although the patient in question showed a compatible clinical picture, it is also symptomatic of other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The infection may be gastrointestinal, pulmonary, cardiac, rhinomaxillary, rhinocerebral-orbital or disseminated 4,5 . It is most common in immunocompromised individuals, patients with uncontrolled diabetes mellitus, hematological malignancy, advanced renal disease or with a transplanted kidney 6 .…”
mentioning
confidence: 99%
“…En este reporte de caso, el diagnóstico histopatológico se realizó a partir de muestras fijadas en formalina buferada al 10% y como en muchos casos no se sospechaba de un proceso micótico en el animal, por lo que cuando se observaron los hongos en el SNC ya no existía la posibilidad de realizar un cultivo, motivo que también describen Pérez & Carrasco. El diagnóstico de meningoencefalitis Zigomicótica se basó en los hallazgos microscópicos y en las característi-cas morfológicas del microorganismo presente en las lesiones del sistema nervioso central, donde los tejidos evaluados microscópicamente con H&E, presentaron lesiones necróticas licuefactivas y hemorrágicas con abundante infiltración eosinofílica, mostrando hifas irregulares ramificadas, septadas o no, reportes descritos también para casos de ZM cerebral en humanos (Sundaram et al, 2005), en bovinos (Munday et al), en bisonte americano y venado, y en ovejas (Riet-Correa et al).…”
Section: Discussionunclassified
“…Diagnosis of zygomycosis was made in accordance with the criteria issued by European Organization for Research and Treatment of Cancer/Mycoses Study Group (13). The clinical forms of zygomycosis have been defined based on the involved organ: rhinocerebral (rhino-orbito-cerebral, rhino-orbital), cutaneous, pulmonary, gastrointestinal, and disseminated (3,9). As well as the clinical findings, radiological imaging methods (computed tomography and magnetic resonance imaging) and endoscopic methods (rhinoscopy, gastrointestinal endoscopy) were used to detect the localization of the infections.…”
Section: Methodsmentioning
confidence: 99%
“…The causative pathogen is usually transported into the body via inhalation through the nasal sinuses. Moreover, direct spore inoculation or exposure of skin already compromised by burns or extensive trauma can lead to the cutaneous form of zygomycosis (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%